2018
DOI: 10.1080/20469047.2018.1508809
|View full text |Cite
|
Sign up to set email alerts
|

Yield of meconium in non-vigorous neonates undergoing endotracheal suctioning and profile of all neonates born through meconium-stained amniotic fluid: a prospective observational study

Abstract: ET: endotracheal; ILCOR: International Liaison Committee on Resuscitation; HIE: hypoxic ischaemic encephalopathy; LMIC: low- and middle-income countries; MAS: meconium aspiration syndrome; MSAF: meconium-stained amniotic fluid; NRP: neonatal resuscitation programme; PPHN: persistent pulmonary hypertension of the newborn; RCT: randomised controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…16 The study done by Viraraghavan VR et al, showed that 3% of vigorous babies and 21.7% of nonvigorous babies developed MAS, which showed statistical significance between non-vigorous neonates and development of MAS (p <0.001). 11 The study done by Gurmeet et al showed that 33% of the cases with MAS expired and 67% of cases with MAS were discharged, which is almost similar to the present study. 8 The number of discharged cases were more than expired cases in patients with MAS, which is similar to the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…16 The study done by Viraraghavan VR et al, showed that 3% of vigorous babies and 21.7% of nonvigorous babies developed MAS, which showed statistical significance between non-vigorous neonates and development of MAS (p <0.001). 11 The study done by Gurmeet et al showed that 33% of the cases with MAS expired and 67% of cases with MAS were discharged, which is almost similar to the present study. 8 The number of discharged cases were more than expired cases in patients with MAS, which is similar to the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The study done by Rokade J et al, showed that 111 patients (56%) delivered by L.S.C.S which is almost similar to present study. 9 Most common maternal age group was between 21 to 30 years which can be comparable to the study done by Vaghela HP et al 10 A 93.7% of babies were vigorous and 6.2% were non-vigorous in present study, which did not match with the study done by Viraraghavan VR et al 11 The study done by Chaudhary R et al, showed that 15 babies (18.07%) required mechanical ventilation, which is similar to . 12 Akmal et al found out that 30% of babies developed MAS, which is similar to and mortality was 15% for those developing MAS.…”
Section: Discussionsupporting
confidence: 57%
“…These results further augment the hypothesis that aspiration of meconium might be an in-utero phenomenon and that routine postnatal tracheal suctioning in NV MSAF neonates might be of limited benefit. 13 38 Comparison of baseline characteristics of the two groups in our study indicated that the “no ET suction” prospective group had a higher proportion of neonates who were of male gender and SGA. Despite the preponderance of such biological factors known to be associated with adverse outcomes such as increased mortality, the incidence of MAS being similar in both the groups is encouraging.…”
Section: Discussionmentioning
confidence: 74%
“…20,21 Viraraghavan et al studied that mortality was significantly higher in the non-vigorous than vigorous neonates with (p<0.001), which is in accordance with our study in which 85% among 20 non vigorous neonates expired. 22 Besides this, intrapartum or postpartum endotracheal suctioning of neonates (vigorous babies) born through MSAF should not be done according to current guidelines, while suggesting expectant management. 23…”
Section: Discussionmentioning
confidence: 99%